Religion and forced displacement in Eastern Europe, the Caucasus, and Central Asia - Hudson, Victoria; Leuştean, Lucian 1967- (Amsterdam University Press, 2022)
This book examines the social and political mobilisation of religious communities towards forced displacement in Eastern Europe, the Caucasus, and Central Asia. It analyses religious strategies in relation to tolerance and transitory environments as a result of the breakup of the Soviet Union and Yugoslavia in the early 1990s, the post-2011 Syrian crisis and the 2014 Russian takeover of Crimea. How do religious actors and state bodies engage with refugees and migrants? What are the mechanisms of religious support towards forcibly displaced communities? The book argues that when states do not act as providers of human security, religious communities, as representatives of civil society and often closer to the grass roots level, can be well placed to serve populations in need. The book brings together scholars from across the region and provides a comprehensive overview of the ways in which religious communities tackle humanitarian crises in contemporary Armenia, Bulgaria, Greece, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Poland, Russia, Serbia, Ukraine and Uzbekistan
Keywords: Vertreibung; Politische Mobilisierung; Flüchtlingshilfe; Humanitäre Intervention; Religiöse Minderheit; Osteuropa; Kaukasus; Mittelasien